KARAKTERISTIK FISIK TANAH DAERAH ALIRAN SUNGAI (DAS) WUNO BAGIAN HULUKABUPATEN SIGI - Anthon monde, Ulfiyah A.rajamuddin, Noviyanti Asnawir jama, (AGROTEKBIS, 2016)
This study has the objective of was to determine the physical characteristics of the soil the upstream watershed (DAS) of Wunosection. This research is as a source of information for the development of land in particular areas of land use, land evaluation, as well as soil and water conservation. Map of slope class, soil maps and land use maps is the overlapping join with using ArcGIS 10.0, thus it obtained six units of land covering the use of forest land (8-15%), forest (15-25%), forest (>40%), shrubs (8-15%), shrubs (>40%)  and cocoa farm. Soil sampling is done randomly on each unit of land, taken three samples except on forest land with a slope (>40%) for each of the undisturb and disturbed soil samples. The results showed that the physical characteristics of the soil on wuno watershed, vary greatly with weight of volume from low to high, the permeability is slow, fast to very fast, Porosity relatively low until high, soil texture dominated by the sand fraction and dust with texture classes clay dusty, and organic matter content is low to moderate.